Тенденції унормування суб’єктного складу проведення конституційної реформи в Україні - Сон, Софія Сергіївна; Сон, С. С.; Son, Sofiia S. (Одеса : Гельветика, 2019)
У статті досліджуються тенденції визначення й унормування суб’єктного складу проведення конституційної реформи в Україні. Виокремлюються роль інститутів громадянського суспільства та доцільність створення Конституційних Зборів як органу установчої влади українського народу.

The article investigates the tendencies of determining and standardizing the constituent entity of carrying out the constitutional reform in Ukraine. The role of institutes of civil society and the expediency of creating a Constitutional Assembly as the organ of the constituent authority of the Ukrainian people are highlighted.
Сон С. С. Тенденції унормування суб’єктного складу проведення конституційної реформи в Україні / С. С. Сон // Юридичний вісник. - Одеса : Гельветика - 2019. - № 2. - С. 27-32.
Keywords: Конституція України; конституційна реформа; Конституційні збори; суб’єкти конституційного права; Research Subject Categories::LAW/JURISPRUDENCE; The Constitution of Ukraine; constitutional reform; the Constitutional Assembly; the subjects of the constitutional rights